Disease and weather induce rapid shifts in a rangeland ecosystem mediated by a keystone species (Cynomys ludovicianus). Issue 1 (20th November 2022) - Duchardt, Courtney J.; Augustine, David J.; Porensky, Lauren M.; Beck, Jeffrey L.; Hennig, Jacob D.; Pellatz, David W.; Scasta, J. Derek; Connell, Lauren C.; Davidson, Ana D.
Abstract: Habitat loss and changing climate have direct impacts on native species but can also interact with disease pathogens to influence wildlife communities. In the North American Great Plains, black‐tailed prairie dogs ( Cynomys ludovicianus ) are a keystone species that create important grassland habitat for numerous species and serve as prey for predators, but lethal control driven by agricultural conflict has severely reduced their abundance. Novel disease dynamics caused by epizootic plague ( Yersinia pestis ) within prairie dog colonies have further reduced prairie dog abundances, in turn destabilizing associated wildlife communities. We capitalized on a natural experiment, collecting data on prairie dog distributions, vegetation structure, avian abundance, and mesocarnivore and ungulate occupancy before (2015–2017) and after (2018–2019) a plague event in northeastern Wyoming, USA. Plague decimated black‐tailed prairie dog populations in what was then the largest extant colony complex, reducing colony cover in the focal area from more than 10, 000 ha to less than 50 ha. We documented dramatic declines in mesocarnivore occupancy and raptor abundance post‐plague, with probability of occupancy or abundance approaching zero in species that rely on prairie dogs for a high proportion of their diet (e.g., ferruginous hawk [ Buteo regalis ], American badger [ Taxidea taxus ], and swift fox [ Vulpes velox ]). Following the plague outbreak, abnormally high precipitation in 2018 hastened vegetation recovery from prairie dog disturbance on colonies in which constant herbivory had formerly maintained shortgrass structure necessary for certain colony‐associates. As a result, we observed large shifts in avian communities on former prairie dog colonies, including near‐disappearance of mountain plovers ( Charadrius montanus ) and increases in mid‐grass associated songbirds (e.g., lark bunting [ Calamospiza melanocorys ]). Our research highlights how precipitation can interact with disease‐induced loss of a keystone species to induce drastic and rapid shifts in wildlife communities. Although grassland taxa have co‐evolved with high spatiotemporal variation, fragmentation of the remaining North American rangelands paired with higher‐than‐historical variability in climate and disease dynamics are likely to destabilize these systems in the future.